Going New Places: Successful Adaptation and Genomic Integrity of Grain Amaranth in India - Akanksha Singh; Markus G. Stetter (Evolutionary Applications)
ABSTRACT Global climate change will impact the geographic distribution of plant populations. The rapid changes will require range shifts and the adaptation of plants. The recent global spread of crops across different continents shows how plants successfully coped with drastically different environments. One such spread was the introduction of the nutritious pseudocereal amaranth to India. Three different species of grain amaranth have been domesticated in different regions of the Americas. The crops have later been introduced to India, likely within the last five centuries, where it is now grown across the subcontinent. We used whole genome sequencing data of over 300 accessions to study the introduction of grain amaranth to India to understand the factors, allowing the successful establishment of crops to novel environments. Despite a population bottleneck during the introduction, Indian amaranths have comparable genetic diversity to those in the Americas. Although gene‐flow between the three grain amaranth species was common in the Americas, the three species did not show signs of gene‐flow in India. Correspondingly, genetic differentiation between species was higher within India than in the native range, indicating strong isolation between otherwise interbreeding populations. We further identified genomic regions under selection in India that potentially enabled the adaptation to the new environment. Our results suggest that introduced crop populations can act as reservoirs of genetic diversity, providing additional adaptive potential and resilience to future environmental change.